OCCURRENCE OF MACRO-B CHROMOSOMES IN ASTYANAX-SCABRIPINNIS PARANAE (PISCES, CHARACIFORMES, CHARACIDAE) - Maistro, E. L.; Foresti, F.; Oliveira, C.; Toledo, LFD (Kluwer Academic Publ, 1992)
B chromosomes occur in several Neotropical fish species. Cytogenetic analysis of 27 specimens (15 females and 12 males) of Astyanax scabripinnis paranae from the Araqua river (a small headwater tributary of the Tiete river) shows that this population has 2n = 50 chromosomes (4M + 30 SM + 4ST + 12A), two chromosome pairs with NORs and conspicuous C-band positive blocks in the terminal position of the long arm of four chromosome pairs. In this population, eight females presented 2n = 51 chromosomes and the extra chromosome was a large metacentric similar in size and morphology to the first chromosome pair in the karotype. This accessory chromosome is entirely heterochromatic in C-banded metaphases and shows a late replication pattern evidenced by BrdU incorporation. There was no significant correlation between the presence of B chromosomes and increased NOR activity at the P >0.05 level. Some aspects related to these B chromosomes are discussed.
Keywords: FISH CYTOGENETICS; B-CHROMOSOMES; BRDU-INCORPORATION; ASTYANAX